2015
DOI: 10.1103/physrevb.91.014433
|View full text |Cite
|
Sign up to set email alerts
|

Role of B diffusion in the interfacial Dzyaloshinskii-Moriya interaction inTa/Co20Fe60B20/MgOnanowires

Abstract: We report on current-induced domain wall motion (CIDWM) in Ta\Co

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 38 publications
18
71
1
Order By: Relevance
“…The DMI vector for two spins with spatial displacement can be written as T P T P T P / , where T P denotes the unit vector pointing from Ta(Pt) to CoFeB and T P , as illustrated in Figure 4(a). Although the spin Hall angles of Ta and Pt are opposite, the T P induced by Pt and Ta on ferromagnetic metals have the same sign 2,21 . Assuming that and T P 0, T P induced from the bottom Ta (top Pt) layer lies in ( ) direction owing to the opposite directions of T P (Fig.…”
Section: /mentioning
confidence: 99%
See 1 more Smart Citation
“…The DMI vector for two spins with spatial displacement can be written as T P T P T P / , where T P denotes the unit vector pointing from Ta(Pt) to CoFeB and T P , as illustrated in Figure 4(a). Although the spin Hall angles of Ta and Pt are opposite, the T P induced by Pt and Ta on ferromagnetic metals have the same sign 2,21 . Assuming that and T P 0, T P induced from the bottom Ta (top Pt) layer lies in ( ) direction owing to the opposite directions of T P (Fig.…”
Section: /mentioning
confidence: 99%
“…We speculate that the diffusion of B atoms in CoFeB during annealling causes the change of . It has been shown that B atoms diffuse towards the interface during the annealing procedure and modify the relative positions of FM and HM atoms at CoFeB/heavy metal interfaces 21 , which in turn is expected to lead to a modified DMI. In addition, a strong accumulation of B in the bottom Ta layer may affect the electronegativity of the heavy metal layer, and hence reverse the sign of .…”
Section: /mentioning
confidence: 99%
“…The breaking of inversion symmetry in noncentrosymmetric crystals, at surfaces or interfaces and the presence of the spin-orbit coupling lead to the appearance of an anisotropic exchange term beyond the isotropic Heisenberg interaction, which is known as the Dzyaloshinskii-Moriya (DM) interaction [1,2]. In collinear ferromagnetic systems, this type of interaction provides domain walls (DWs) with a chiral character [3][4][5][6][7][8], plays a key role in DW dynamics [9][10][11][12], and leads to the stabilization of isolated chiral skyrmions [13][14][15][16]. It may also cause the formation of noncollinear magnetic states [7,17] such as spin spirals [18,19] and condensated skyrmionic phases [16,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been reported recently that in Ta/CoFeB/MgO, the amount of boron present at the interface may in°uence D via modi¯cation of local atomic con¯g-uration. 120 As the boron di®usion signi¯cantly depends on the material used for the HM layer (unpublished results), it is di±cult to determine the degree of such contribution to the DMI for all the structures studied here. Further investigation is required to clarify quantitatively the origin of DMI at the HM/CoFeB interface.…”
Section: The Interface Dzyaloshinskii-moriya Interactionmentioning
confidence: 99%